Rare diagnosis in a neonate with isolated skin lesions - Suresh, Supriya Gujjar; Jagadeesan, Saraswathy; Srinivasan, Arathi; Scott, Julius Xavier (International Journal of Contemporary Pediatrics, 2017)
Langerhan Cell Histiocytosis (LCH) represents a group of diseases with varied spectrum of presentation. LCH limited to skin is not very common with 100 cases reported in literature. A definitive diagnosis is important for both management and follow up. A 30 days old male infant was brought with vesiculopustular skin lesions over the trunk and back since day 12 of life. Systemic examination was normal. Preliminary investigations revealed a normal haemogram with normal liver and renal function tests. He was initially managed symptomatically. In view of persisting skin leisons, biopsy done was suggestive of Langerhans Cell Histiocytosis and confirmed by CD1a postivity on immunohistochemistry. Skeletal survey did not reveal any lytic leison, bone scan was normal. There was no biochemical evidence of diabetes insipidus. The child was diagnosed to have neonatal isolated cutaneous LCH. He was followed up periodically without any therapy. Presently, he has an Event Free Survival (EFS) of 2 years without any progression. Though isolated cutaneous Langerhan Cell Histiocytosis is rare in neonates, it should still be considered in the differential diagnosis by the treating paediatrician. Though it can be a self-limiting entity, it is very important to recognize this condition, since it is mandatory to look for multisystem involvement by LCH as it determines the treatment intensity. It is essential to closely follow up these children to know if this heralds involvement of risk organs by LCH or a self-limiting disorder. This case also highlights the multidisciplinary dialogue required in the diagnosis and management of such rare cases.